“This is it. This should be enough” : negotiations of Neoliberal performative empowerment in selected contemporary women-centric television series - Broodryk, Chris Willem (University of Pretoria, 2025)
Dissertation (MA (Drama and Film Studies))--University of Pretoria, 2024.